Pengaruh Strategi Pembelajaran Berbasis Multimedia Interaktif Terhadap Hasil Belajar Fisika pada Materi Optika Geometri - Selli Mariko (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
This research aims to identifying differences in learning outcomes between students who were taught with multimedia-based learning strategy and learning outcomes of students who are taught with strategies based learning modules. The study was quasi experimental with pretest-posttest kontrol group design. Population are students of class XI SMK Muhammadiyah 1 Temon. Samples were selected by random sampling techniques to determine the experimental class and kontrol class. While to know the results of higher learning between the kontrol and experimental groups were tested with Scheffe test.